PENINGKATAN SIKAP PERCAYA DIRI ANAK MELALUI PENERAPAN METODE SOSEOPREUNER DI KELOMPOK A BUSTHANUL ATHFAL RESTU 1 MALANG - Uswatun Khasanah; Anwar Sa’dullah; Ika Anggraheni (UNISMA, 2019)
Children's self-confidence is one of the important things that must be developed, identification of problems that exist in this study are: 1) children do not dare to appear, 2) children find it difficult to express wishes and opinions with simple sentences to friends or others, and 3) children indifferent to his friend's artwork the lack of insight of the teacher in choosing the right learning method made the researcher use the soseopreuner method. This study uses the class action research method (CAR), with two cycles which include activities of planning, action, observation, and reflection. The results showed that the implementation of the soseopreuner method in BA RESTU 1 Malang was said to be successful in increasing children's self-confidence in A1 BA RESTU 1 Malang because there was an increase in the percentage of children who met the completeness criteria in the child's self-confidence through the first cycle as many as 58.80% rose to 89.93% in the second cycle which was criteria and an increase of 75% of the total number of children. So that from observing the first cycle and second cycle it can be concluded that the increase in children's self-confidence has experienced a relative increase.